Teilhard De Chardin's Spirituality of the Cross - Faricy, Robert L. (Horizons, 1976)
This article studies the spiritual theology of the cross in the writings of Pierre Teilhard de Chardin. In Teilhard's books and articles the accent falls on the cross as a symbol of progress. The cross stands for Jesus' positive act of saving the world through his death; it represents, too, Christian life as a sharing in the cross of Jesus through the labor and pain of human progress. In his spiritual notes, however, Teilhard takes a different perspective. His own meditations on the cross center not on the cross as a positive symbol of personal and collective progress through struggle, but rather on death as the ultimate fragmentation, and as an apparent dead end that is the final passage to Jesus Christ.